2020
DOI: 10.3390/insects11080489
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding: A Reliable Method for the Identification of Thrips Species (Thysanoptera, Thripidae) Collected on Sticky Traps in Onion Fields

Abstract: Several thrips species (Insecta, Thysanoptera) are globally known as important crop pests and vectors of viral diseases, but their identification is difficult because of their small body size and inconspicuous morphological differences. Sequencing variation in the mitochondrial cytochrome c oxidase I (COI) region has been proven to be useful for the identification of species of many groups of insect pests. Here, DNA barcoding has been used to identify thrips species collected with the use of sticky traps place… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 25 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…In recent years, the study of the mitochondrial regions of DNA including COI, using molecular biology, has proved useful in understanding some biological aspects of onion thrips populations [20]. The phylogenetic analysis of COI sequences supported the thelytokous reproductive mode of T. tabaci infesting Welsh onion.…”
Section: Discussionmentioning
confidence: 98%
“…In recent years, the study of the mitochondrial regions of DNA including COI, using molecular biology, has proved useful in understanding some biological aspects of onion thrips populations [20]. The phylogenetic analysis of COI sequences supported the thelytokous reproductive mode of T. tabaci infesting Welsh onion.…”
Section: Discussionmentioning
confidence: 98%
“…The maximum likelihood phylogenetic tree based on mitochondrial gene revealed that L. oleae is well separated from all other Liothrips species ( Figure 3 ). As recently described, Marullo et al [ 44 ] also successfully distinguished some thrips species of the same genera based on mt- COI gene sequences. Furthermore, COI gene sequencing possibly identifies unknown specimens by comparing their COI sequence, and it has been used for identification purposes in projects known as species barcoding.…”
Section: Discussionmentioning
confidence: 97%
“…Two different COI haplotypes were detected for adult and larval specimens collected from different host plants in different municipalities. Marullo et al [55], recently demonstrated that DNA barcoding is a reliable tool for identifying genetic differences within the same thrips population. Our results revealed some genetic variation due to the presence of two haplotypes collected in the same location (Trescore Cremasco, where more specimens were collected and barcoded) and on the same host plant (C. betulus).…”
Section: Discussionmentioning
confidence: 99%